Applicability of the Spanish Version of the Supports Intensity Scale (SIS), in the Mexican Population with Severe Mental Illness (Revista Latino-Americana de Enfermagem, 2010)
This study presents the results obtained from the evaluation, by specialist judges, of the Supports Intensity Scale (SIS), Spanish version, to determine its suitability for the Mexican population with severe mental illness (SMI). The instrument, originally designed for people with intellectual disabilities, is consistent with the multidimensional concept of quality of life and the social model of disability. The semantic equivalence of the items adjusted by specialist judges, the reliability of the subscales, using Cronbachs alpha, and the concurrent validity between the SIS and the Global Functioning Assessment (GAF) were analyzed. The mean similarity to the original was 9.91 from a total of 10 (sd=0.14). The reliability coefficients were above 0.95 and the correlations between the SIS and the GAF were medium to high and significant. In conclusion, in the Mexican context, the SIS scale can be used to understand the needs and expectations of people with mental illness.